Influence of capnographic training with biological feedback on the physical performance and hemodynamics in sportsmen - L. V. Kapilevich (Bûlleten' Sibirskoj Mediciny, 2012)
The influence of capnographic training with biological feedback (BF) on character of leg hemodynamics and physical performance has been studied in sportsmen training in cyclic sports. The capnographic FB training favors an increase in the efficiency of oxygen use by muscles, optimizes the level of tissue respiration, favors the faster adaptation of blood flow to metabolic needs of leg skeletal muscles, and, finally, provides an increase in the physical performance of sportsmen. The results obtained allow us to consider the capnographic training with biological feedback as a promising component of the training process in cyclic sports.